2007
DOI: 10.1158/1535-7163.mct-06-0254
|View full text |Cite
|
Sign up to set email alerts
|

The rGel/BLyS fusion toxin specifically targets malignant B cells expressing the BLyS receptors BAFF-R, TACI, and BCMA

Abstract: B lymphocyte stimulator (BLyS) is crucial for B-cell survival, and the biological effects of BLyS are mediated by three cell surface receptors designated B cellactivating factor receptor (BAFF-R), transmembrane activator and calcium modulator and cyclophilin ligand interactor (TACI), and B-cell maturation antibody (BCMA). Increased expression of BLyS and its receptors has been identified in numerous B-cell malignancies. We generated a fusion toxin designated rGel/BLyS for receptor-mediated delivery of the reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 37 publications
1
48
1
Order By: Relevance
“…rGeloninBLyS, a recombinant toxin-BLyS fusion ligand, has been shown to target BAFF-R in LBCL and MCL cell lines. 51 Our recent studies indicate that BAFF-R binds rGelonin-BLyS and migrates to the nucleus resulting not only in lymphoma cell apoptosis in vitro, but also in severe combined immunodeficiency (SCID) mouse LBCL BLOOD, 7 MAY 2009 ⅐ VOLUME 113, NUMBER 19 For personal use only. on May 12, 2018.…”
Section: Discussionmentioning
confidence: 99%
“…rGeloninBLyS, a recombinant toxin-BLyS fusion ligand, has been shown to target BAFF-R in LBCL and MCL cell lines. 51 Our recent studies indicate that BAFF-R binds rGelonin-BLyS and migrates to the nucleus resulting not only in lymphoma cell apoptosis in vitro, but also in severe combined immunodeficiency (SCID) mouse LBCL BLOOD, 7 MAY 2009 ⅐ VOLUME 113, NUMBER 19 For personal use only. on May 12, 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an alternative approach was developed to target malignant B-cell lines (45) or chronic lymphocytic leukemia (46) by fusing the ligand BlyS (also known as BAFF) with a xenogeneic recombinant protein toxin, gelonin. This ligand-toxin fusion protein, rGel/BlyS, was tested for potency and selectivity on several different B-cell lines that included mantle cell lymphoma, diffuse large B-cell lymphoma, and MM (45).…”
Section: Discussionmentioning
confidence: 99%
“…This ligand-toxin fusion protein, rGel/BlyS, was tested for potency and selectivity on several different B-cell lines that included mantle cell lymphoma, diffuse large B-cell lymphoma, and MM (45). The greatest potency of rGel/BlyS was observed on mantle cell lymphoma and diffuse large B-cell lymphoma cell lines, with IC 50 values of 1 to 5 pmol/L.…”
Section: Discussionmentioning
confidence: 99%
“…Although rGel-based immunotoxins have been used in the treatment of malignant cancers for more than 15 years, the actual mechanisms behind the induction of cell death have remained unclear (46,47). In this study, we showed that C6.5/rGel fusions had no effect on apoptosis-related mechanisms (PARP cleavage, TUNEL, and DNA fragmentation) or necrosis-related mechanisms (LDH release).…”
Section: Discussionmentioning
confidence: 59%